Penilaian Jaket Anak dengan Hiasan Teknik Smock - Annisa Rahmawati, Dinda; Suryawati, Suryawati; Sesnawati, Yeni (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
This study aims to obtain an assessment of children's jacket products using batik pemalang cloth with grombyang motif with smock technique decoration based on aspects of product quality, design elements and design principles. This research method uses quantitative descriptive. This study produced 5 children's jacket products with smock technique decorations which were assessed by 5 panelists with instrument data collection techniques using mixed questionnaires. The research instrument consisted of 21 statements and 2 questions. This rating is measured using a rating scale. The assessment was carried out using product quality theory according to W. H. Mayall and design element theory and design principles according to Wolfe. Based on the product quality aspect which consists of sub-aspects of maximum results, attractive appearance, and diverse shapes get a score of 90.1%. Furthermore, the aspect of design elements consisting of texture and color sub-aspects received a score of 85.4%. Then the aspect of design principles consisting of the sub-aspects of balance, harmony, and proportion received a score of 93.4%. In the emphasis sub-aspect, overall, the emphasis on the entire design lies in the smock. The product with the highest final assessment result in design 2 obtained a score of 92.3% and the lowest final assessment result in design 3 obtained a score of 88.3%.